Understanding the demand for medical care by the elderly in Kedah: A preparation towards population ageing - Samsudin, Shamzaeffa; Abdullah, Norehan; Applanaidu, Shri Dewi; Abu Bakar, Nor'Aznin; Lim, Hock Eam; Majid, Rahimah (Universiti Utara Malaysia, 2013)
Understanding factors that affect health care demand by the elderly is vital for a health system to be more responsive in providing care to this special group.Since health care demand studies at micro level are rather limited within Malaysia context, this research attempts to reduce the gap by focusing on elderly demand.The objectives of this study are to (i) profile the medical care utilisation of the elderly by demographic factors, (ii) identify the existence of income-related inequity in health care utilisation among older age groups, and (iii) identify the role of living arrangements of the elderly on health care utilisation among the elderly in Kedah state.There are two types of demand used for this study, which are doctor visits and inpatient stays.A multistage cluster sampling was used in selecting the sample for the study.A total number of 399 of respondents aged 62 to 98 were interviewed face-to-face using a structured questionnaire.The probit and Poisson model with robust variance estimates were used in estimating the demand equation.It is found that income, after controlling for other socioeconomic and health related factors, is statistically significant in affecting the likelihood of doctor visits, but not the frequency.There is no evidence of income-related inequity for inpatient stays. The role of living arrangement, as measured by marital status and the number of individual aged 18 and over living together, however, is not so profound. Some control variables, on the other hand, show a significant effect. This is evident that health condition is not the only factor that determines health care demand of the elderly in Kedah state.The findings from this analysis imply that the government’s policy to reduce income inequality may indirectly control the income-related inequity in health care demand. In addition, support programs in the community need to be intensified to raise awareness of health and consequently reduce unnecessary visits to health services.